(untitled) (Research, Society and Development, 2021)
Two-dimensional imaging records, as conventional radiographies, are part of the orthodontic clinic routine; frontal sinus images are often present in these exams. The characteristics of the frontal sinus are information of great relevance for the Forensic Sciences, as their images may be used for human identification purposes. With the advent of new three-dimensional technologies and computerized image examinations such as Computed Tomography (CT), three-dimensional analysis of the frontal sinuses has become possible. This article evaluates the possibilities of human identification using frontal sinuses 2D and 3D images and the role of orthodontists in this context. Pubmed, SciELO, LILACS and Web of Science were used as databases. As inclusion criteria, were selected texts concerning the studied issue. Although the analysis of frontal sinuses is traditionally carried out using two-dimensional images, there is a growing trend of studies employing CT scans. Cone-Beam Computed Tomography (CBCT) is an important diagnosis tool, more frequently used in orthodontics, which allows a three-dimensional approach and great precision in measurements. Together with two-dimensional analysis of frontal sinuses, 3D images are of great value for human identification. Although three-dimensional analysis is not yet a routine, its Forensic use is undoubtedly an excellent tool provided by new technologies. It is important that the orthodontist knows this possibility by properly keeping the patients’ imaging exams.